Induction of cellulase production in Trichoderma reesei by a glucose–sophorose mixture as an inducer prepared using stevioside. Issue 27 (13th June 2022) - Zhang, Peng; Li, Qian; Chen, Yudian; Peng, Nian; Liu, Wenshu; Wang, Xuemei; Li, Yonghao
Abstract : Inducing the synthesis of active cellulase is critical for biorefineries. The effective inducer was prepared from stevioside, which contains sophorose. Abstract : Sophorose is currently the most effective inducer of cellulase production by Trichoderma reesei ; however, the use of byproduct sophorose from the stevioside acid hydrolysis process has not been developed. In this study, stevioside was hydrolysed with different concentrations of HCl to obtain isosteviol and a mixture of glucose and sophorose (MGS). Isosteviol showed good inhibitory effects on the growth of Aspergillus niger, Saccharomyces cerevisiae and Escherichia coli after separation. At the same time, MGS, as a byproduct, was evaluated for cellulase production to determine the feasibility of this approach. MGS was compared with common soluble inducers, such as lactose, cellobiose, and a mixture of glucose and β-disaccharide (MGD), and induced higher cellulase production than the other inducers. The cellulase activity induced by MGS was 1.64- and 5.26-fold higher than that induced by lactose and cellobiose, respectively, and was not significantly different from that induced by MGD. The crude enzyme using MGS as an inducer with commercial β-glucosidase was further tested by hydrolyzing NaOH-pretreated corn stover with 5% solid loading, and 33.4 g L −1 glucose was released with a glucose yield of 96.04%. The strategy developed in this work will be beneficial for reducing inducer production cost through a simple stevia glycoside hydrolysis reaction and will contribute to studies aimed at improving cellulase production using soluble inducers for easier operation in industrial-scale cellulase production.